Anti-inflammatory coupled anti-angiogenic airway stent effectively suppresses tracheal in-stents restenosis - Yanan Zhao; Yiming Liu; Jiheng Shan; Xiaohong Xu; Chengzhi Zhang; Zaoqu Liu; Xiaomeng Li; Zhaoqian Zhong; Yanxia Gao; Kewei Ren; Dechao Jiao; Jianzhuang Ren; et al. (Journal of Nanobiotechnology)
Abstract Excessive vascularization during tracheal in-stent restenosis (TISR) is a significant but frequently overlooked issue. We developed an anti-inflammatory coupled anti-angiogenic airway stent (PAGL) incorporating anlotinib hydrochloride and silver nanoparticles using advanced electrospinning technology. PAGL exhibited hydrophobic surface properties, exceptional mechanical strength, and appropriate drug-release kinetics. Moreover, it demonstrated a remarkable eradication effect against methicillin-resistant Staphylococcus aureus. It also displayed anti-proliferative and anti-angiogenic properties on human umbilical vein endothelial cells and lung fibroblasts. PAGL was implanted into the tracheae of New Zealand rabbits to evaluate its efficacy in inhibiting bacterial infection, suppressing the inflammatory response, reducing angiogenesis, and attenuating excessive fibroblast activation. RNA sequencing analysis revealed a significant downregulation of genes associated with fibrosis, intimal hyperplasia, and cell migration following PAGL treatment. This study provides insight into the development of airway stents that target angiogenesis and inflammation to address problems associated with TISR effectively and have the potential for clinical translation.